2010
DOI: 10.1103/physrevb.81.245115
|View full text |Cite
|
Sign up to set email alerts
|

Cd doping effects in the heavy-fermion compoundsCe2MIn8(M=Rha

Abstract: Low-temperature magnetic properties of Cd-doped Ce 2 MIn 8 ͑M = Rh and Ir͒ single crystals are investigated. Experiments of temperature-dependent magnetic-susceptibility, heat-capacity, and electrical-resistivity measurements revealed that Cd doping enhances the antiferromagnetic ͑AFM͒ ordering temperature from T N = 2.8 K ͑x =0͒ to T N = 4.8 K ͑x = 0.21͒ for Ce 2 RhIn 8−x Cd x and induces long-range AFM ordering with T N = 3.8 K ͑x = 0.21͒ for Ce 2 IrIn 8−x Cd x . Additionally, x-ray and neutron magnetic scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The magnetic coupling of the Ce atoms within the unit cell can be determined by comparing the experimental integrated intensity of several magnetic peaks with the calculated model (Eq. 1) [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic coupling of the Ce atoms within the unit cell can be determined by comparing the experimental integrated intensity of several magnetic peaks with the calculated model (Eq. 1) [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been essential in a number of high-profile cases, as for example the orbital and charge ordering in transition metals [94][95][96][97][98][99][100][101], frustrated magnetism in low dimensional magnetic systems [102,103], multiferroics [104,105], heavy fermion antiferromagnets [106,107], picnide superconductors [108][109][110], magnetic thin films and multilayers [111,112].…”
Section: Discussionmentioning
confidence: 99%
“…For Ce MIn 5 (m = 1, n = 1) it was found that Cd suppresses the superconductivity for M = Co and Ir while it tends to favor AFM ordering for M = Rh [8,9]. For Ce 2 MIn 8 (m = 2, n = 1: Ce 218) Cd doping increases the T N for M = Rh and induces a long range magnetically ordered phase for M = Ir [10]. All these previous results suggested that Cd is acting as an electronic tuning agent that induces a decrease of the local density of states at the Ce 3+ site which tends to reduce the Kondo effect and favor AFM ordering [11,12].…”
Section: Introductionmentioning
confidence: 99%